Imagining The 18th Islam in Mataram Court: Structure of Thinking of Javanese Islam in Babad Tanah Jawi - Hambali Hambali; Achmad Fawaid; Faridy Faridy; Moh. Fachri (JURNAL AT-TURAS, 2024)
This study seeks to examine the Islamic life behind the palace walls in the Babad Tanah Jawi by R.Ng. Yasadipura I. In all historical studies on the 'Islamization of Java', the Babad Tanah Jawi is almost always quoted, because this text tells a lot about the transition of palace power, the involvement of the guardians, to the court's conspiracy with the Dutch. This study aims to explore one aspect that according to the author, Babad Tanah Jawi researchers rarely take, namely aesthetic politics. R.Ng. Yasadipura I can be said to be a political subject, because he has a long and intimate history with Islam on the one hand, but he lives in the great tradition of Javanese royalty on the other. He was a court servant who was asked to write about the greatness of Javanese kings on the one hand, but he was also known as a poet who was subversive to the kingdom on the other. He lived in the circle of the great Mataram Pakubuwana IV kingdom, but he was also a descendant of Jaka Tingkir whose story was 'marginal' in the historiography of Mataram and Demak. That is, R.Ng. Yasadipura I refuses to be identified in a particular social class. It is 'political' because he is able to migrate from one social class to another.